Analisa Kinerja Keuangan Untuk Keputusan Pemberian Kredit Pada Bank Mandiri KCP Belawan - Siahaan, Hans Sebastian Sejahtera; Harahap , Ramadhan (Journal of Community Research and Service, 2025)
The purpose of this research is to find out "Financial Performance Analysis for Credit Granting Decisions at BankMandiri KCP Belawan". This study uses a qualitative descriptive research method. Qualitative research is an approach used toinvestigate the situation of natural objects, where the researcher plays the role of the main instrument, using a combination ofdata collection techniques (Sugiyono, 2009). In this context, the study aims to analyze financial performance for the decision toprovide credit to a bank. The data collected from respondents' responses can be used as research information. The source of datawas obtained from the debtor and Bank Mandiri KCP Belawan with the completeness of the required documents. Two types ofdata were collected in this study: primary data and secondary data. Data collection techniques through observation, interviewsand documentation. This study aims to determine the influence of Financial Performance Analysis on Credit Granting Decisionsat Bank Mandiri KCP Belawan. The results of this study are the factors that can make credit applications accepted by the bankare (1) the debtor already has an official business license and NPWP, (2) the debtor must have 50% capital before applying forcredit and the business is managed directly by the debtor himself, (3) the debtor must be cooperative and open when asked abouthis business for credit management, (4) The debtor has never had a history of arrears of payment. (5) The debtor has never beeninvolved in legal problems, (6) The value of the collateral given by the debtor must be in accordance with the market price whenapplying for credit, (7) The business that has been established has been running for approximately 1 year, (8) The location ofthe business is easy to reach by local residents. If a business has no debt (current debt = 0), both the current ratio and the quickratio cannot be calculated in the usual way and are considered undefined or infinity, then this shows that the business has a verystrong liquidity condition because there are no short-term obligations that need to be fulfilled.